Fabrication and Pilot In Vivo Study of a Collagen-BDDGE-Elastin Core-Shell Scaffold for Tendon Regeneration - Sandri, Monica; Filardo, Giuseppe; Kon, Elizaveta; Panseri, Silvia; Montesi, Monica; Iafisco, Michele; Savini, Elisa; Sprio, Simone; Cunha, Carla; Giavaresi, Gianluca; Veronesi, Francesca; Fini, Milena; et al. (Frontiers in Bioengineering and Biotechnology, 2016)
The development of bio-devices for complete regeneration of ligament and tendon tissues is presently one of the biggest challenges in tissue engineering. Such device must simultaneously possess optimal mechanical performance, suitable porous structure and biocompatible microenvironment. This study proposes a novel collagen-BDDGE-elastin (CBE)-based device for tendon tissue engineering, by the combination of two different modules: i) a load bearing, non-porous, 'core scaffold', developed by braiding CBE membranes fabricated via an evaporative process; ii) a hollow, highly porous, 'shell scaffold', obtained by uniaxial freezing followed by freeze-drying of CBE suspension, designed to function as a physical guide and reservoir of cells to promote the regenerative process. Both core and shell materials demonstrated good cytocompatibility in vitro and, notably, the porous shell architecture directed cell alignment and population within the sample. Finally, a prototype of the core module was implanted in a rat tendon lesion model and histological analysis demonstrated its safety, biocompatibility and ability to induce tendon regeneration. Overall, our results indicate that such device may have the potential to support and induce in situ tendon regeneration.